2022
DOI: 10.1055/s-0042-1757454
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Infections in Low Birth Weight Neonates

Abstract: Objective Our objective was to evaluate the incidence of urinary tract infections (UTIs) in low birth weight (LBW) neonates and to evaluate the compliance of neonatal intensive care unit (NICU) providers in performing urine cultures as a part of late-onset sepsis (LOS) evaluations following an educational intervention. Study Design A retrospective chart review for all LBW infants undergoing LOS evaluations was performed. An educational intervention was conducted to encourage NICU providers to perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This cohort of infants had a 6.4% overall incidence of urinary tract infections, and, interestingly, 78% were BPT infants. Studies suggest a urine culture should be part of workups to evaluate preterms for LOS [ 47 ]. Because we did not collect decision data, there is no way of knowing how a decision to obtain a urine culture was made when an infant was showing signs and symptoms of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…This cohort of infants had a 6.4% overall incidence of urinary tract infections, and, interestingly, 78% were BPT infants. Studies suggest a urine culture should be part of workups to evaluate preterms for LOS [ 47 ]. Because we did not collect decision data, there is no way of knowing how a decision to obtain a urine culture was made when an infant was showing signs and symptoms of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…UTI is one of the most common infections in preterm infants in NICUs, presenting a high incidence around the world. 2 , 3 , 39–41 In our center, urine cultures were routinely performed through catheterization when infants present with nonspecific manifestations associated with infection, especially among those at more than one week of age, and a relatively high incidence of UTI was yielded. Similar to other preterm infant populations, 2–4 , 40 , 41 the pathogen spectrum of UTIs in this study was dominated by the Enterobacteriaceae family, including pathogenic organisms Klebsiella and Escherichia .…”
Section: Discussionmentioning
confidence: 99%
“…Historically, an overarching perspective concerning UTIs in preterm infants emphasized the bloodstream as the origin of UTI pathogens. 2 , 3 , 7 However, in light of the increasing emphasis on the gut as a repository of UTI pathogens in other populations 8–11 , 35 and the unfavorable intestinal microbial features of preterm infants, 13 , 14 , 16 we investigated the relationship between gut microbiota and UTIs in preterm infants. Through longitudinal observation, our results revealed that UTI infants with different pathogens exhibited distinct microbial development trajectory.…”
Section: Discussionmentioning
confidence: 99%